Role of Toll-like receptors polymorphisms in the development of extremely severe COVID-19 - Lyudmila A. Ashchina; N. I. Baranova; O. A. Kulieva; A. I. Bolgova (Инфекция и иммунитет)
COVID-19 is a respiratory disease caused by the SARS-CoV-2 virus that can proceed to acute respiratory distress syndrome (ARDS) and trigger immunopathological mechanisms that lead to excessive inflammation. Toll-like receptors, as pattern recognition receptors, play an indispensable role in virus identification and activate the innate immune system, which can lead to the secretion of proinflammatory cytokines such as IL-1, IL-6, TNFα, and type I IFN. Antiviral toll-like receptors, including TLR3, TLR7, and TLR9, can activate the TRIF-dependent pathway, induce the production of proinflammatory cytokines, chemokines, and type I and type III interferons, participate in recognition of dsRNA and detection of unmethylated CpG DNA. In addition, an important role of TLR2 in COVID-19, which recognizes peptide glycans on the surface of gram-positive bacteria, and TLR4, which recognizes gram-negative bacteria lipopolysaccharide and plays a role in hyperinflammation in COVID-19, has been shown. It was confirmed that TLRs can be involved both in the initial failure of virus clearance and in the subsequent development of severe COVID-19 clinical manifestations mainly acute respiratory distress syndrome (ARDS) with fatal respiratory failure. The aim of this work was to study the polymorphisms of TLR3 (rs3775291), TLR9 (rs352140), TLR7 (rs3853839), TLR4 (rs4986790), TLR4 (rs4986791), TLR2 (rs574708) in patients with COVID-19 depending on disease outcome. The study included 187 patients, of whom 157 recovered and 30 deceased. Genetic analysis for polymorphisms of the TLR3 (rs3775291), TLR9 (rs352140), TLR7 (rs3853839), TLR4 (rs4986790), TLR4 (rs4986791), TLR2 (rs574708) genes was performed by real-time PCR. Statistical processing of the obtained results was performed using Statistica 12.0 (USA) software. The inter-group difference was considered statistically significant at p 0.05. The strength of associations was estimated and presented as odds ratio (OR) and 95% confidence interval. It was noted that the genotypes GC TLR7 (rs3853839), AG TLR2 (rs574708), GG TLR4 (rs4986790), TT TLR4 (rs4986791) can be predictors of a fatal COVID-19 outcome. On the contrary, the genotypes GG TLR7 (rs3853839), AA TLR2 (rs574708), AA TLR4 (rs4986790), CC TLR4 (rs4986791) can be protective and contribute to the recovery of patients.